Proceedings of the 7th International Conference on Multimedia Systems 2016
DOI: 10.1145/2910017.2910627
|View full text |Cite
|
Sign up to set email alerts
|

Live streaming of 4K ultra-high definition video over the internet

Abstract: HTTP Adaptive Streaming (HAS) is the de facto standard for video streaming services over the Internet. In HAS, each video is temporally segmented and stored in different qualities. The client selects the quality level for every video segment based on network conditions, allowing a smooth playback with the best possible Quality of Experience (QoE). Although results are promising, current solutions suffer from two problems. First, a low quality and large end-to-end latency are often observed in live streaming sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, it is shown that when using 1s segments, server push itself does not introduce any benefit in live stream latency. In [24], the authors further reduced the segment length to as low as 0.1s. They designed an SDN controller to prioritize video traffic and hence reduce buffering.…”
Section: Qoe Improvement Techniques Of Http Live Streamingmentioning
confidence: 99%
“…However, it is shown that when using 1s segments, server push itself does not introduce any benefit in live stream latency. In [24], the authors further reduced the segment length to as low as 0.1s. They designed an SDN controller to prioritize video traffic and hence reduce buffering.…”
Section: Qoe Improvement Techniques Of Http Live Streamingmentioning
confidence: 99%
“…Mirshokraie et al optimized video encoding using layered encoding for peer-to-peer streaming [40]. Other transmission optimization techniques to improve live streaming include the use of HTTP/2 to reduce the number of requests [31,45], a hybrid of broadband and multicast [36], optimization of TCP congestion control [7], multiserver streaming [12], scheduling users to different CDNs [65], and selective retransmission of frames [50].…”
Section: Related Workmentioning
confidence: 99%
“…In several publications so far, this topic has been discussed, problems identified and several solutions proposed. However, in most cases, these solutions suffer from low quality, large end-to-end latency in live streaming and frequent freezes in the video playout due to sudden drops of the available bandwidth [22]. In [22], it was shown network-based prioritization introduced by an OpenFlow, SDN-enabled controller can reduce video freezes caused by network congestion.…”
Section: Ultra/high Definition Live Video Streaming In Wireless Networkmentioning
confidence: 99%